Modelling The Effect Of Particle Breakage In Comminution Machine - Ahmad, Norazirah (2019)
In this study, determination of breakage distribution and understanding of complex nature particle breakage took in comminution process were investigated. The test work involved the drop weight test, single particle size fraction batch test, standard Bond test and point load test. The tests are conducted to obtain the breakage characteristic of three types of rock which is clinker, limestone and granite. The breakage characteristic of different size fractions (maximum 20 mm and minimum 6.3 mm) and shape (granular, spherical and flaky) were examined at various input energy, Ecs express in kWh/t. The relation between specific comminution energy level and the breakage index (t10) was established on the size fractional base. As expected, the coarser particles tend to generate more fragments than the smaller ones. Furthermore, the three methods (BI, BII and BIII) are used to analyze one size fraction batch test. These test consists of grinding material samples which are clinker, limestone and granite in a batch laboratory scale ball mill, for a selected period of time. The BIII method was considered to give most accurate breakage function and value of three variables β,γ and φ were calculated. However, the only one size fraction most reliable to be used for data fitting which is -3.35mm + 2.36mm. Overall after fitting the size range for the three samples clinker, limestone and granite obtained γ more than 1.3 but not reach 2. The value of β within 1.1 to 2.12 and φ value less than 1 for all samples. The trend showing similar for all types of rock samples. In conclusion, the different size shows significant effect in determined the breakage function where it involve high impact energy or low impact energy during comminution process.